Salivary oxytocin has nonlinear relationships with trust and reciprocity - Sakura Arai; Motoki Watabe; Kei Kanari; Qiulu Shou; Frank Krüger; Haruto Takagishi (Games, 2023)
Oxytocin has been proposed to regulate human trust. Previous experiments supported this claim by demonstrating that exogenous and endogenous oxytocin is associated with trust (how much trust people place in strangers) and reciprocity (how much people reciprocate when trusted). However, recent replication attempts have been unsuccessful in demonstrating the trust-enhancing effect of oxytocin, and there is limited evidence on whether oxytocin is associated with reciprocity. This study aimed to replicate the previously found nonlinear relationships between the endogenous oxytocin concentration and both trust and reciprocity by utilizing a monetarily incentivized trust game. In a college sample, we found that salivary oxytocin levels showed (i) an inverted U-shaped relationship with trust in men and (ii) a U-shaped relationship with reciprocity in women. The current results confirm the previous finding that endogenous oxytocin levels have nonlinear relationships with trust and reciprocity. Further research on the role of oxytocin secretion in trust and reciprocity is warranted.
Keywords: 330; oxytocin; trust; reciprocity; trust game